Virtual screening and experimental validation of small-molecule compounds targeting AR in prostate cancer - Zhongqiang Fan; Xuexue Hao; Weiren Chen; Zhunan Xu; Qihua Wang; Muwei Li; Hao Zhang; Congzhe Ren; Yutong Chen; Jianping Lin; Xiaoqiang Liu (Molecular Diversity, 2025)

VascuConNet: an enhanced connectivity network for vascular segmentation - Muwei Jian; Ronghua Wu; Wenjin Xu; Huixiang Zhi; Chen Tao; Hongyu Chen; Xiaoguang Li (Medical & Biological Engineering & Computing, 2024)

Functional correlation tensors in brain white matter and the effects of normal aging - Lyuan Xu; Yurui Gao; Muwei Li; Richard Lawless; Yu Zhao; Kurt G. Schilling; Baxter P. Rogers; Adam W. Anderson; Zhaohua Ding; Bennett A. Landman; John C. Gore (Brain Imaging and Behavior, 2024)
Resting state correlations between blood oxygenation level dependent (BOLD) MRI signals from voxels in white matter (WM) are demonstrably anisotropic, so that functional correlation tensors (FCT) may be used to quantify the underlying microstructure of BOLD effects in WM tracts. However, the overall spatial distribution of FCTs and their metrics in specific populations has not yet been established, and the factors that affect their precise arrangements remain unclear. Changes in WM occur with normal aging, and these may be expected to affect FCTs. We hypothesized that FCTs exhibit a characteristic spatial pattern and may show systematic changes with aging or other factors. Here we report our analyses of the FCT characteristics of fMRI images of a large cohort of 461 cognitively normal subjects (190 females, 271 males) sourced from the Open Access Series of Imaging Studies (OASIS), with age distributions of 42 y/o – 95 y/o. Group averages and statistics of FCT indices, including axial functional correlations, radial functional correlations, mean functional correlations and fractional anisotropy, were quantified in WM bundles defined by the JHU ICBM-DTI-81 WM atlas. In addition, their variations with normal aging were examined. The results revealed a dimorphic distribution of changes in FCT metrics with age, with decreases of the functional correlations in some regions and increases in others. Supplementary analysis revealed that females exhibited significant age effects on a greater number of WM areas, but the interaction between age and sex was not significant. The findings demonstrate the reproducibility of the spatial distribution of FCT metrics and reveal subtle regional changes with age.

Disrupted white matter functional connectivity in aMCI APOEε4 carriers: a resting-state study - Hua Lin; Muwei Li; Yang Zhan; Li Lin; Kun Yang; Shimin Hu; Ying Han (Brain Imaging and Behavior, 2021)